Prediksi Curah Hujan Bulanan Kabupaten Trenggalek Tahun 2022 dan 2023 Menggunakan Metode ARIMA - Rafi Prayoga Dhenanta; Isna Binti Kholifah (Politeknik Statistika STIS, 2022)
Rainfall was a climate measurement used as a proxy for the numbers of rain water dropped on a certain place and time of measurement. Monthly rainfall was usually used as a basis on determining the planting season of some farm commodities, eg. rice that had become Indonesian main energy source for years. Knowing the forecast of rainfall would help the farmers, moreover if their fields were rain fed, schedule their planting season or even help them choose the commodities to plant. This research used ARIMA time series model for modeling historical data of rainfall in Trenggalek Regency and then forecasting the model up to two years in the future. This approach resulted in the model that best suited the data was ARIMA(0,1,1)(0,1,0) with seasonality of 12 using Box-Cox transformation beforehand. Lastly, this result was applied in agricultural sector to determine the planting times of rice in Trenggalek Regency.